SALESPERSON’S SUPPORT SYSTEMS: OPTIMIZING JOB PERFORMANCE IN THE NIGERIAN PHARMACEUTICAL INDUSTRY (American Journal of Business Management, Economics and Banking, 2024)
This study investigates the relationship between Salesperson Support Systems (SSS) and Job Performance (JP) in the pharmaceutical industry in the South-South region of Nigeria. Through the use of cross-sectional survey design, data were administered and collected from 170 sales representatives transversing 25 pharmaceutical firms within the region under review. The size of the study sample was determined using Taro Yamane’s formula however, the purposive sampling technique guided the questionnaire distribution. The research findings specify a positive and statistically significant relationship between the proxies of the Salesperson Support Systems (SSS) and Job Performance (JP), signifying those organizational mechanisms; management support, technological devices (tools), training initiatives, and performance monitoring are critical to salesforce performance discourse. Consequently, the outcomes of the findings highlight that Salesperson Support Systems (SSS) is catalyst of sales efficiency and ultimately enhance job performance in a vastly competitive business environment. In conclusion, prioritizing and implementing an all-inclusive support system is critical in improving job performance and sustaining a competitive edge. Practical implications reflect on the need to integrate salesforce support systems with strategic goals and ensuring that support system’s outlay would translate into quantifiable performance increases.